Brain abscess potentially secondary to periodontal infection resulting in death of a young patient - Bonardi, J. P. [UNESP]; Silva, L. F. [UNESP]; Momesso, G. A.C. [UNESP]; de Lima, V. N. [UNESP]; Pereira, R. S. [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Faverani, Leonardo Perez [UNESP] (Wiley, 2019)
This study aimed to report a case of a 17-year-old female patient referred to the oral and maxillofacial surgery (OMS) team from Santa Casa de Araçatuba who was unconscious, had a Glasgow coma score of 3, and was diagnosed by a neurosurgeon with brain death. Her mother reported that the patient showed no systemic disease. The patient underwent a supragingival curettage after completion of an orthodontic treatment. One day after the procedure, the patient showed oedema at the canine superior right space and fluctuation point. After the abscess was drained, there was a worsening of clinical condition. The patient was referred to the Intensive Care Unit and showed only a leukocytosis (approximately 17 000 mm³). The OMS team observed a tissue necrosis on her right superior lip extending to the lower eyelid on the same side and oedema of the periorbital region. On computed tomography sections, hypodense images affecting the larger part of the right cerebral hemisphere were observed, suggestive of brain abscess. Unfortunately, the patient showed no response and her condition evolved to brain death, as diagnosed by electroencephalogram tests performed three times every 12 h. It is necessary to be highly careful with even minimal signs of infection, because we never know the aggressiveness of the bacteremia.
Keywords: brain abscess; death; focal infection